Do Multiple Mini-Interview and Traditional Interview Scores Differ in Their Associations With Acceptance Offers Within and Across Five California Medical Schools?. (August 2018) - Jerant, Anthony; Henderson, Mark C.; Griffin, Erin; Hall, Theodore R.; Kelly, Carolyn J.; Peterson, Ellena M.; Wofsy, David; Franks, Peter
Abstract : Purpose: In single-school studies, multiple mini-interview (MMI) and traditional interview (TI) scores are associated with acceptance offers. Unexamined is whether scores at one school are associated with acceptance at other schools; such analyses would mitigate single-school design biases and better estimate how well interviews capture desired applicant attributes. Using data from the 5 California Longitudinal Evaluation of Admissions Practices (CA-LEAP) medical schools, the authors examined associations of MMI and TI scores with acceptance offers within and across schools. Method: The analyses included applicants who interviewed at ≥1 CA-LEAP school during the 2011–2013 admissions cycles. Three CA-LEAP schools employed TIs and 2 employed MMIs. Interview scores were standardized ( z scores: mean = 0, SD = 1), and associations with acceptance offers were examined within and across schools in analyses stratified by school, adjusting for applicant sociodemographics, academic metrics, year, and total number of interviews. Results: Of 4, 993 applicants interviewed, 428 (8.6%) interviewed at both MMI schools, 681 (13.6%) at ≥2 TI schools, and 1, 327 (26.6%) at ≥1 MMI and ≥1 TI school. For each school, acceptance was associated with interview score at that school and also with interview scores at the other 4 schools. Cross-school associations of MMI versus TI scores with acceptance did not differ statistically. Conclusions: Interview score at a given school was associated with acceptance at the other 4 schools, with no significant differences in associations for MMIs versus TIs. The findings suggest both MMIs and TIs captured attributes valued by admissions teams across CA-LEAP schools.